Chiral Phthalimides Demonstrated Bactericidal Effect Against Multi Drug Resistant Hyper Virulent Klebsiella Pneumonia - Israr Ali Khan, Salman Ahmad, Fahad Ullah, Falak Niaz, Sajid Iqbal, Ejaz Ali Khan, Momin Khan, Sher Wali Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Bacterial resistance to antibiotics is global issue. Many antibiotics which is used is used in common practice against bacterial strain are no more effective against it. Same is the case of hyper virulent Klebsiella pneumoniae (hvKp) mostly clinical isolates of this bacteria are multi drug resistant and can cause a verity of infections. Our study aims to screen five novel chiral phthalimides (1, 3 dioxoisoindolin-2-y1)-4-methytopheonic acid labelled as FIB, 2-(1, 3-dioxoisoindlin-2y1)-4(methythio) butamic acid (FIC), 2-(1,3dioxoisoindolin-2yl)-3 meracaptopropanic acid (FIF) 2-(1-3-dioxoisoindolin-2yl)-3(4-hydroxyphnyl prophanic acid(FIH) and 3-(1, 3 dioxoisoindolin-2yl) prophanic acid (FII) against multi drug resistant hvKp and to check its cytotoxic effect against human red blood cells (RBC’s). Activity of these compounds were measured through different techniques e.g. Agar well diffusion, disc diffusion and macro broth dilution method. Minimum inhibitory concentration (MIC) of these compounds were measured as well. All five compounds were bactericidal and were observed with different concentration of inhibition e.g. MIC for FIC, FIB, FII, FIF and FIH against hvKp were 6mg/ml, 25mg/ml, 25mg/ml, 50mg/ml and 100mg/ml. This result show that FIC have strong activity against hvKp as compared to other compounds. None of these five compounds were toxic to human RBC’s. Chiral phthalimides showed strong antibacterial activity against hvKp and were none toxic to human RBC’s.